2011
DOI: 10.1097/01.epx.0000399178.79516.a3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with cesarean deliveries at Women Specialized Hospital Riyadh, King Fahd Medical City, Kingdom of Saudi Arabia

Abstract: Increasing maternal age and parity as well as prematurity were the factors significantly associated with CS. Fetomaternal outcome was comparable between vaginal and abdominal deliveries, despite the high CS rate. Non-reassuring cardiotocography was the most common indication. Secondary tests for evaluation of fetal well being might help to reduce the high CS rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Previous reports showed that fetal distress, previous cesareans and breech presentation were the most common indications for cesarean delivery in a tertiary level hospital in Jeddah, KSA [ 14 ]. Kamil et al observed that fetal distress was the commonest indication for cesareans at Women Specialized Hospital Riyadh, King Fahd Medical City, KSA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports showed that fetal distress, previous cesareans and breech presentation were the most common indications for cesarean delivery in a tertiary level hospital in Jeddah, KSA [ 14 ]. Kamil et al observed that fetal distress was the commonest indication for cesareans at Women Specialized Hospital Riyadh, King Fahd Medical City, KSA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal age and parity were the most associated factors for cesareans, and fetal distress was the commonest indication for cesareans at Women Specialized Hospital Riyadh, King Fahd Medical City, Kingdom of Saudi Arabia [ 23 ]. In the current study; repeated cesarean delivery, failure to progress, fetal distress; breech, antepartum haemorrhage, hypertension and diabetes mellitus were the main indications of cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Kamil A et al found that pre-maturity of the fetus, parity and advanced age of the mother were prominent risk factors for increased rates of cesarean section. 14 The authors recommended that certain secondary tests should be done during pregnancy to ensure that fetus is all right and this may help reduce the cesarean section delivery rates. 14 Ahmed I et al noted the effect of counselling on the rates of cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…14 The authors recommended that certain secondary tests should be done during pregnancy to ensure that fetus is all right and this may help reduce the cesarean section delivery rates. 14 Ahmed I et al noted the effect of counselling on the rates of cesarean section. 15 They observed that the rates of the cesarean section were more among women who were not given counselling during pregnancy and who were not attended by full time faculty.…”
Section: Discussionmentioning
confidence: 99%